2023
DOI: 10.1177/10760296231151710
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Prolonged Oral Anticoagulation for the Prevention of Thromboembolic Events in Patients Recovered From COVID-19 1 Year After Hospital Discharge: The SARCOV-19 Prospective Registry

Abstract: Our objective in this study is to know the predictors of thromboembolic events 1 year after hospitalization for severe COVID-19 and the benefit of preventive oral anticoagulation for 1 month to placebo after release. We conducted a prospective study to determine the benefit of preventive anticoagulation upon discharge from the hospital and to determine the predictive factors of thromboembolic events. We included 720 patients in the SARCOV-19 Registry, with a mean age of 62.07 (±18.11), and 61.1% male. After 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…This speculation is supported by a recent report from the SARCOV-19 registry evaluating 30 days of anticoagulation in COVID-19 patients upon hospital discharge. Of note, consistent with our data, the authors were able to demonstrate a reduction of thromboembolic events during a FU of 1 year ( Aidouni et al, 2023 ). While the described results seem only hypothesis-generating, the large ongoing double-blind, placebo-controlled randomized control ACTIV-4c trial (NCT04650087) is currently evaluating midterm cardiovascular outcomes (90 days) after a 30 days regime of prophylactic apixaban started upon hospital discharge ( Ortel, 2023 ).…”
Section: Discussionsupporting
confidence: 91%
“…This speculation is supported by a recent report from the SARCOV-19 registry evaluating 30 days of anticoagulation in COVID-19 patients upon hospital discharge. Of note, consistent with our data, the authors were able to demonstrate a reduction of thromboembolic events during a FU of 1 year ( Aidouni et al, 2023 ). While the described results seem only hypothesis-generating, the large ongoing double-blind, placebo-controlled randomized control ACTIV-4c trial (NCT04650087) is currently evaluating midterm cardiovascular outcomes (90 days) after a 30 days regime of prophylactic apixaban started upon hospital discharge ( Ortel, 2023 ).…”
Section: Discussionsupporting
confidence: 91%
“…In studies 19 , 39 , 41 investigating the postdischarge prophylaxis for postdischarge patients, postdischarge prophylaxis demonstrated a statistically significant lower risk of venous thromboembolism compared to no prophylaxis (RR, 0.49; 95% CI: 0.31–0.76) (Fig. 7 A).…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, three studies investigated the use of additional antiplatelet therapy, primarily P2Y12 agonists, with one study also including aspirin in the treatment. Furthermore, three studies 19 , 39 , 41 explored postdischarge prophylaxis and four studies 15 , 16 , 18 , 40 explored prophylactic anticoagulation for outpatients, with one study 18 using LMWH (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 A recent study of preventive anticoagulation upon hospital discharge found that prolonged preventive anticoagulation lowered the risk of thrombotic events without a corresponding increase in the risk of bleeding. 23 However, conflicting results regarding the risk of thromboembolism are being reported, and the consensus regarding which participants to be involved in preventive anticoagulation is scant. Stevens et al 24 demonstrated that the risk of COVID-19related thromboembolism is lower among ambulatory patients, but the risk was not lower among hospitalized patients who had COVID-19 vaccination.…”
Section: Discussionmentioning
confidence: 99%